Farmers’ tendency towards using solar energy technology (renewable energy) in the Nubaria region: - Habeba, Hany Mohamed; El-Kholy, Shaimaa Abdel-Mageed; Ibrahim, Eman Mostafa (Journal of agricultural, environmental and veterinary sciences, 2022)
Objectives: The main objective of the current study was to determine the level of farmers’ tendency towards domestic and farmable uses of solar energy technology, as well as the variables associated with the degree of farmers’ inclination towards domestic and farmable uses of solar energy technology. In addition, it aims to identify farmers’ orientation towards knowledge resources for domestic and farmable uses of solar energy technology, as well as identify issues that limit its use. This study was conducted in the Tiba, Nubaria region, with the Adam village chosen to perform the current study, including 1004 farmers. A random sample of 104 farmers enrolled to represent 10% of the total sample size. Data was collected and analyzed using a personal interview questionnaire. Pearson’s correlation coefficient, the chi-square test, the phi coefficient, the Cronbach’s alpha stability coefficient, frequencies, percentages, and the arithmetic mean were all used. Results: The data of the current study have revealed the following: -The level of farmers’ tendency towards the uses of solar energy technology in domestic and farmable uses was average, estimated at 55,8 %. Furthermore, there was a significant relationship between the farmers’ tendency towards the uses of solar energy technology in domestic and farmable uses. There was also a significant correlation between each of the following independent variables: the age of subjects, the number of family members, number of years of education of the participants, average value of the electricity bill, having household appliances, participation in agricultural extension activities, degree of ambition, immersion in local community affairs, membership of organizations, adequacy of the family’s monthly income, practical and professional status of the respondent. -The order of sources from which farmers obtain information in this area in descending order: television programs with 91.3 %, representatives of solar energy companies with 76.0%, parents and relatives with 64.4 %, then the Internet with 53.8%, extension publications, solar companies by 49.0 %, and neighbors and friends by 47.1 %. -The study participants also unanimously agreed that the most significant problems are those correlated with the farmable and domestic uses of solar energy technology, followed by problems related to farmers, and finally problems associated with the farmable uses of solar energy technology.